Sexuality and menopause - Fierro, Delcy (2015)
In 106 women attended at the gynecological outpatient service, we found that sexual activity and sexual desire decrease after menopause, mainly because of less sexual desire, not explained by 60% of patients. Patients with history of pelvic surgery had less satisfactory sexual relations. Sexual initiative of Peruvian postmenopausal women is minimal.